Mental Health and Quality of Life in Keningau, Sabah - Rathakrishnan, Balan (Jurnal Psikologi dan Kesihatan Sosial, 2025)
Youth mental health is an increasingly important public health issue, particularly in rural and semi-urban settings such as Sabah. However, empirical evidence on youths’ psychological well-being in this region remains limited. This study aims to assess mental health status and quality of life among youths in Keningau District, Sabah. This quantitative study involved 93 youths and employed descriptive analysis. Mental health indicators included stress, anxiety, depression, and suicide risk, while quality of life was assessed across physical, psychological, social relationship, and environmental domains. The results indicate that most youths experienced low to moderate levels of psychological distress and generally good quality of life. However, social relationships emerged as the weakest domain, and a small proportion of youths were identified as having significant suicide risk. These findings underscore the importance of holistic mental health interventions that strengthen social support and community environments.